A socio-economic impact study of Japanese tourism in the Philippines - Bonifacio, Glenda Lynna Tibe (Glenda Lynna Tibe Bonifacio, 1990)
Tourism is considered by government planners and social scientists as a strategy of development for many developing countries. The Philippines is no exception.